THE RELATIONSHIP BETWEEN SELF-CARE AGENCY AND MEDICATION ADHERENCE IN TUBERCULOSIS PATIENTS - Iswatun, Iswatun; Wijayanti, Endah Sri; Susanto, Joko; Umam, Khotibul; Rindayati, Rindayati (Universitas Airlangga, 2025)
Introduction: Adherence to tuberculosis (TB) medication is a critical factor in curing patients. Incomplete or improper treatment can lead to drug resistance or the recurrence of infection. Self-care agency plays a vital role in helping individuals remain compliant and consistent with their treatment. High medication adherence can also enhance an individual’s self-care agency. This study aims to determine the relationship between self-care agency and medication adherence in TB patients at Lamongan Health Center. Methods: This study utilized a quantitative correlational design with a cross-sectional approach. The study was conducted in March 2023. The study population consisted of 65 TB patients, with a sample size of 56 respondents selected through simple random sampling. The independent and dependent variables were self-care agency and medication adherence, respectively. Data on self-care agency were collected using the ASA Scale questionnaire, and medication adherence was assessed using the MMAS-8 questionnaire. Data analysis was performed using the Spearman rank correlation test. Results: The study found a strong positive relationship between self-care agency and medication adherence in TB patients at Lamongan Health Center, with a significance level of 0.001 (p < 0.05) and a correlation coefficient of 0.635. TB patients with high self-care agency were more likely to adhere to their medication regimen compared to those with lower self-care agency. Conclusions: The findings of this study suggest that improving self-care agency can enhance medication adherence among TB patients. These results can serve as a reference for strategies aimed at increasing medication adherence by strengthening patients' self-care agency.